Extraocular Motor System Exhibits a Higher Expression of Neurotrophins When Compared with Other Brainstem Motor Systems - Hernández, Rosendo G.; Silva-Hucha, Silvia; Morcuende, Sara; de la Cruz, Rosa R.; Pastor, Angel M.; Benítez-Temiño, Beatriz (Frontiers in Neuroscience, 2017)
Extraocular motoneurons resist degeneration in diseases such as amyotrophic lateral sclerosis. The main objective of the present work was to characterize the presence of neurotrophins in extraocular motoneurons and muscles of the adult rat. We also compared these results with those obtained from other cranial motor systems, such as facial and hypoglossal, which indeed suffer neurodegeneration. Immunocytochemical analysis was used to describe the expression of nerve growth factor, brain-derived neurotrophic factor and neurotrophin-3 in oculomotor, trochlear, abducens, facial and hypoglossal nuclei of adult rats, and Western blots were used to describe the presence of neurotrophins in extraocular, facial (buccinator) and tongue muscles, which are innervated by the above-mentioned motoneurons. In brainstem samples, brain-derived neurotrophic factor was present both in extraocular and facial motoneuron somata, and to a lesser degree, in hypoglossal motoneurons. Neurotrophin-3 was present in extraocular motor nuclei, while facial and hypoglossal motoneurons were almost devoid of this protein. Finally, nerve growth factor was not present in the soma of any group of motoneurons, although it was present in dendrites of motoneurons located in the neuropil. Neuropil optical density levels were higher in extraocular motoneuron nuclei when compared with facial and hypoglossal nuclei. Neurotrophins could be originated in target muscles, since Western blot analyses revealed the presence of the three molecules in all sampled muscles, to a larger extent in extraocular muscles when compared with facial and tongue muscles. We suggest that the different neurotrophin availability could be related to the particular resistance of extraocular motoneurons to neurodegeneration.